2014
DOI: 10.2320/matertrans.m2014301
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Type 316L Stainless Steel during Cyclic Deformation under Cell Culturing

Abstract: Dissolution and repassivation of type 316L stainless steel during cyclic deformation were examined in a simulated body environment. Samples were exposed to simulated body fluid (SBF) with or without cells, and then subjected to cyclical deformation in the SBF kept at cell culturing condition. The cyclic stress ratio and maximum stress were 0.1 and 300 MPa, respectively. Transients of stress, strain and corrosion potential were recorded during the test.The corrosion potential became less noble immediately after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Most structural materials are often subjected to not only atmospheric corrosion but also to dynamic mechanical factors including wear and fatigue (14,15). For example, suspension spring coil of automobiles is exposed to the corrosion wear during contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Most structural materials are often subjected to not only atmospheric corrosion but also to dynamic mechanical factors including wear and fatigue (14,15). For example, suspension spring coil of automobiles is exposed to the corrosion wear during contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has previously reported that mechanical stress breaks down the passive film and induces localized corrosion of metallic materials. [14][15][16] For example, Ti alloy and stainless steel, which are used as biomedical implants, form a passive film and show high corrosion resistance in the environment of the human body; however, the passive film is broken when it is subjected to fatigue stresses due to the movements of the body such as walking. 16 The implants that are exposed to mechanical stress are expected to have a shorter lifetime when compared to those without mechanical stress.…”
mentioning
confidence: 99%
“…Thus, we have performed a series of studies on stainless steels as biomaterials, [30][31][32][33] investigating their corrosion behaviors, and surface modi cations for improvement of osseoconductivity. Such surface modi cations have the potential to promote the application of stainless steels as implant materials.…”
Section: Introductionmentioning
confidence: 99%